Mortality among contraceptive pill users: cohort evidence from Royal College of General Practitioners’ Oral Contraception Study - Hannaford, Philip C (BMJ Publishing Group Ltd., 2010)
Objective To see if the mortality risk among women who have used oral contraceptives differs from that of never users. Design Prospective cohort study started in 1968 with mortality data supplied by participating general practitioners, National Health Service central registries, or both. Setting 1400 general practices throughout the United Kingdom. Participants 46 112 women observed for up to 39 years, resulting in 378 006 woman years of observation among never users of oral contraception and 819 175 among ever users. Main outcome measures Directly standardised adjusted relative risks between never and ever users for all cause and cause specific mortality. Results 1747 deaths occurred in never users of oral contraception and 2864 in ever users. Compared with never users, ever users of oral contraception had a significantly lower rate of death from any cause (adjusted relative risk 0.88, 95% confidence interval 0.82 to 0.93). They also had significantly lower rates of death from all cancers; large bowel/rectum, uterine body, and ovarian cancer; main gynaecological cancers combined; all circulatory disease; ischaemic heart disease; and all other diseases. They had higher rates of violent deaths. No association between overall mortality and duration of oral contraceptive use was observed, although some disease specific relations were apparent. An increased relative risk of death from any cause between ever users and never users was observed in women aged under 45 years who had stopped using oral contraceptives 5-9 years previously but not in those with more distant use. The estimated absolute reduction in all cause mortality among ever users of oral contraception was 52 per 100 000 woman years. Conclusion Oral contraception was not associated with an increased long term risk of death in this large UK cohort; indeed, a net benefit was apparent. The balance of risks and benefits, however, may vary globally, depending on patterns of oral contraception usage and background risk of disease.